2018
DOI: 10.1002/jmv.25218
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of torque teno virus DNA load in saliva and plasma following allogeneic hematopoietic stem cell transplantation

Abstract: Plasma torque teno virus (TTV) DNA load directly correlates with the degree of T-cell immune reconstitution early after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Here, the kinetics of oral TTV DNA shedding was examined to assess whether quantitation of TTV DNA load in saliva may either replace or complement that in plasma for predicting lymphocyte (ALC) reconstitution after engraftment. This prospective observational study enrolled 38 nonconsecutive allo-HSCT recipients. Saliva and plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
3
18
2
Order By: Relevance
“…TTV has been shown to be present in human saliva [8,9]. In a patient who underwent an allogeneic hematopoietic stem cell transplant, detection of TTV was more frequent and the TTV titer was higher in saliva as opposed to plasma [9].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…TTV has been shown to be present in human saliva [8,9]. In a patient who underwent an allogeneic hematopoietic stem cell transplant, detection of TTV was more frequent and the TTV titer was higher in saliva as opposed to plasma [9].…”
Section: Introductionmentioning
confidence: 98%
“…In a patient who underwent an allogeneic hematopoietic stem cell transplant, detection of TTV was more frequent and the TTV titer was higher in saliva as opposed to plasma [9]. This led the authors to suggest that quantitation of TTV in saliva may be of value in predicting immunocompetence after engraftment [8].…”
Section: Introductionmentioning
confidence: 99%
“…11 As TTV is ubiquitous, and viral replication correlates with immune status, TTV has been studied as a promising marker to assess global functional immune competence in, for example, transplant recipients. [12][13][14][15][16][17][18][19][20] TTV has not been demonstrated to cause any disease in humans.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] We previously reported that although overall TTV DNA levels in saliva and plasma tended to correlate, they may follow different kinetics in allo-HSCT recipients, thereby suggesting that the level of TTV replication could be compartment dependent. 16 In addition, TTV DNA can be detected in stools from healthy people and patients with enteritis. 17 On the basis of this evidence, 16,17 we hypothesized that the kinetics of TTV DNA load in the gastrointestinal tract early after allo-HSCT may allow us to anticipate aIGvHD occurrence.…”
mentioning
confidence: 99%
“…16 In addition, TTV DNA can be detected in stools from healthy people and patients with enteritis. 17 On the basis of this evidence, 16,17 we hypothesized that the kinetics of TTV DNA load in the gastrointestinal tract early after allo-HSCT may allow us to anticipate aIGvHD occurrence.…”
mentioning
confidence: 99%